Analisis Kesalahan Berbahasa pada Spanduk dan Pamplet dijalan Raya dalam Kajian Morfologi - Audina, Fitra; Dewi, Lusi Cantika; Septiandi, Muhammad Fichri; angkat, Puriandari; Arizki, Aqsol (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine language errors in the field of morphology on banners. And pamphlets. This study used descriptive research using the listening, photographing and note-taking method, namely obtaining data by listening to the use of language. In the use of language, errors often occur, both spoken and written, which deviate from the rules of the language and are not in accordance with the enhanced Spelling EYD. The use of language or processes in language can lead to language errors which are closely related to the language learning process. Language errors occur in speech both orally and in writing as at the morphological level with these language errors, and it is very important to have an analysis of language errors. Language errors on banners on the highway in the field of morphology are mostly related to written language, including: the use of standard and non-standard words. Based on the data found and analyzed, it can be concluded that writing on banners still often encounters language errors at the morphological level related to word writing. This study examines eight data relating to standard and non-standard word errors. Keywords: language errors, morphology, banners, pamphlets